ANALISIS EFISIENSI ALOKATIF USAHA TANI TAMBAK IKAN BANDENG (Chanos chanos F) DI KABUPATEN ACEH UTARA - . Riani (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
Milkfish is a fishery resource produced of aquaculture. This farming could be profitable if it is produced with optimal production. However, the milkfish productivity by fish farmers in North Aceh District was very low. Because were not efficient production factors used. The purpose of this study is to determine the factors that influence the production and the level of technical and economical efficiency of fish farming ponds. Cross section data o used in the survey.This data was analyzed by using stochastic frontier production and efficiency test. The research showed that the significant factors affecting the production of pond fish farming were the area of land, spindles, pesticides and feed. The fishponds in the research area  had not reached the allocative efficiency.The research  suggested that farmers  optimize the production factors significantly consisting of like land, spindles, pesticides and feed to get full efficiency